A Randomized, Single‐dose, Phase I Clinical Comparison of a Trastuzumab Biosimilar With a Reference Trastuzumab Formulation in Healthy Chinese Male Volunteers. Issue 2 (1st November 2022) - Pu, Huahua; Jia, Jingying; Zhao, Chunyang; Hou, Sheng; Guo, Huaizu; Li, Jing; Qian, Weizhu; Wang, Hao; Sun, Chan; Zou, Yang
Abstract: The test drug, a recombinant humanized monoclonal antibody, is a biosimilar candidate for the reference drug. The purpose of this study was to evaluate the bioequivalence of these two drugs. The study was divided into two parts, a pre‐study and a formal trial. The pre‐study included two subjects who were each given a single intravenous infusion of 6 mg/kg test drug. The formal trial was designed to be a randomized, double‐blind, parallel controlled trial in which 70 subjects were randomly assigned 1:1 to receive either test or reference drug as a single 6 mg/kg intravenous infusion. In the pre‐study, the immunogenicity was negative in both subjects and the safety of the test drug was considered to be good. The two groups in the formal trial had similar demographic characteristics. The 90% confidence interval of geometric mean ratios of area under the serum concentration‐time curve from the time 0 to the time of last quantifiable concentration, area under the serum concentration‐curve from time 0 to infinity, and maximum observed serum concentration between the test group and the reference group fell between 80% and 125% and the bioequivalence was recognized. There was no significant difference in the positive rate of antidrug antibodies. The treatment‐emergent adverse events in the test group were similar to those in the reference group. This study showed that the test drug has similar pharmacokinetics, immunogenicity, and safety to the reference drug in healthy male subjects.